Model of thermal conductivity of anisotropic nanodiamond - Dudnik, S.F.; Kalinichenko, A.I.; Strel’nitskij, V.E. (Вопросы атомной науки и техники, 2014)
Dependence of thermal conductivity of nanocrystalline diamond on grain size and shape is theoretically
investigated. Nanodiamond is considered as two-phase material composed of diamond grains characterizing by three
main dimensions and segregated by thin graphite layers with electron, phonon or hybrid thermal conductivity.
Influence of type of thermal conductance and thickness of boundary layer on thermal conductivity of nanodiamond
is analyzed. Derived dependences of thermal conductivity on grain dimensions are compared with experimental
data. Теоретически исследуется зависимость теплопроводности нанокристаллического алмаза от величины и
формы кристаллита. Наноалмаз рассматривается как двухфазный материал, состоящий из алмазных зерен,
характеризующихся тремя главными размерами и разделенных тонкими графитовыми слоями с
электронной, фононной или смешанной теплопроводностью. Анализируется влияние типа
теплопроводности пограничного слоя и его толщины на теплопроводность наноалмаза. Полученные
зависимости теплопроводности наноалмаза от размеров зерна сравниваются с имеющимися
экспериментальными данными. Теоретично досліджується залежність теплопровідності нанокристалічного алмазу від величини й форми
кристаліту. Наноалмаз розглядається як двофазний матеріал, що складається з алмазних зерен, що
характеризуються трьома головними розмірами, та розділених тонкими графітовими прошарками з
електронною, фононною або змішаною теплопровідністю. Аналізується вплив типу теплопровідності
прикордонного шару і його товщини на теплопровідність наноалмазу. Отримані залежності
теплопровідності наноалмазу від розмірів зерна порівнюються з наявними експериментальними даними.